The Role of Leadership in Managing Organisational Culture Change in the Context of Information Technology Implementation - Agustian Zen; Selfi Yanti; Mahargi Rizki Hutomo; Kraugusteeliana Kraugusteeliana; Herman Yosef Arisutama (Jurnal Minfo Polgan, 2023)
The rapid development of information technology has affected many organisations in various sectors. The implementation of information technology often involves changes in work processes, organisational structure and overall organisational culture. The background of this study aims to investigate the role of leadership in managing organisational culture change in the context of information technology implementation. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study arrived at a statement that in the context of information technology implementation in organisations, organisational culture change becomes a critical factor affecting the success and sustainability of the use of such technology. Leadership plays an important role in managing such organisational culture change. Through effective communication, appropriate education and training, active participation and involvement of organisational members, strong team building, recognition and rewards, gradual change management, and continuous evaluation and adjustment, leadership can create an enabling environment for the adaptation and utilisation of information technology.